KiwiSaver: Comparing Survey and Administrative Data - Anton Samoilenko; David Law (New Zealand Government, The Treasury, 2014)
This paper explores the KiwiSaver information contained in two sources: the administrative data from the Inland Revenue Department (IRD) and the Survey of Family, Income and Employment (SoFIE). In particular, the paper explores the membership and contribution information, explaining significant patterns and highlighting any differences that exist between the two data sources. At the aggregate level, the paper shows noticeable difference in membership levels, tenure, annual employer and employee contributions and total cumulative contributions. At the individual level, regression results identify the main determinants of the observed differences and quantify their impact.
Keywords: E21; D91; 330; Altersvorsorge; Sozialstatistik; Datenqualität; Vergleich; Sozialversicherung; Befragung; Neuseeland